Mercury concentrations in the surface sediments of the intertidal area along the west coast of Peninsular Malaysia - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (2003)
Total mercury (Hg) levels in the intertidal surface sediments along the west coast of Peninsular Malaysia were analysed by using heat vaporization method. Total Hg levels in these sediments ranged from 3.00 to 201 μg kg -1 dry weight with a mean concentration of 60.0 μg kg -1 dry weight. More than 90% of the samples studied have the total Hg concentrations less than 150 μg kg-1 dry weight. Compare with the regional data and sediment quality guidelines, the Hg contamination in the intertidal area along the west coast of Peninsular Malaysia was not serious, except for a few sites that might have received anthropogenic Hg in the samples collected between 1999 and 2000. It is suggested that a similar study of heavy metals in the sediments of the west coast of Peninsular Malaysia be conducted regularly.